2005
DOI: 10.1021/jp0502609
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Mutual Diffusion Coefficient for Dodecyl Acrylate in Low Molecular Weight Poly(dodecyl acrylate) with Laser Line Deflection (Wiener's Method) and the Fluorescence of Pyrene

Abstract: Diffusion of small molecules into glassy polymers is quite complicated and almost always non-Fickian. Little work has been done with the diffusion of low molecular weight polymers that are liquids at room temperature (such as poly(dodecyl acrylate)) into their miscible monomers. We have studied three molecular weights under 20 000 to determine if poly(dodecyl acrylate) diffusion into dodecyl acrylate could be treated with Fick's law and if so to determine the values of the diffusion coefficients. We compare tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Figure 4 illustrates a variable transition zone. Figure 5 presents the fluid displacement and the streamlines after 1,000 s for a transition zone width increasing from 0.2-5 mm and with k = 2 × 10 −9 N. In all cases the diffusion coefficient was fixed at 10 −6 cm 2 s −1 , which was experimentally determined by Antrim et al (2005).…”
Section: Variable Transition Zone Widthmentioning
confidence: 99%
“…Figure 4 illustrates a variable transition zone. Figure 5 presents the fluid displacement and the streamlines after 1,000 s for a transition zone width increasing from 0.2-5 mm and with k = 2 × 10 −9 N. In all cases the diffusion coefficient was fixed at 10 −6 cm 2 s −1 , which was experimentally determined by Antrim et al (2005).…”
Section: Variable Transition Zone Widthmentioning
confidence: 99%
“…Such a rotational dependence is also seen with immiscible systems. They observed that interfacial width did not grow with the expected √ t dependence although the DDA-pDDA system was previously shown to follow Fick's law in a static configuration [3]. We proposed that diffusion weakens the EIT, which allows the drop to stretch.…”
Section: Dodecyl Acrylate In Poly(dodecyl Acrylate)mentioning
confidence: 88%
“…For example, they are used in polymer chemistry to study changes in free volume of polymers as a function of polymerization reaction parameters, molecular weight, and crosslinking, [27][28][29][30] in cell physiology to study cell membrane viscosity which is linked to Radial pumping is accomplished with syringe pump. The distance b between the two plates of the Hele-Shaw cell is set to 0.65 mm.…”
Section: A Molecular Probementioning
confidence: 99%